Sagayan: The Dance of Meranao Royalty - Maruhom, Sahria (JPAIR Multidisciplinary Research, 2013)
The paper examined the origin and historical background of Sagayan war dance, the dance of Meranao Royalty. Specifically it sought to answer the following aspects of Sagayan war dance 1) To determine the meaning of Sagayan war dance; 2) To describe how Sagayan war dance is being performed by the players including its traditional costumes and significance; and, 3) To describe the implications of Sagayan war dance in terms of good leadership and governance. The study used the descriptive design involving research techniques with the support of various Meranao materials found in the libraries of Mindanao State University maincampus, but other public and private schools located in Marawi City and Lanao Del Sur, which is the setting of the study. Aside from the materials found in the library, the researcher conducted personal interview to key informants who are knowledgeable on Sagayan war dance. The results show that in most occasions, Sagayan war dance is performed before any celebration or gathering. The study concludes that the Sagayan war dance conveys masculinity and bravery, attributes needed by leaders in the discharge of public duties.